Differences of Citizen's Sociology Learning Results Learn Package C Program Before and Time Covid-19 Pandemic - Puji Rosaldy; Syuraini Syuraini (Universitas Negeri Padang, 2021)
This research was motivated by the learning outcomes of citizens studying sociology subjects in the SPNF-SKB Package C program in Pariaman City. The purpose of this study was to determine the differences in the learning outcomes of learning residents on sociology subjects in the SPNF-SKB Package C program in Pariaman City.This type of research is a type of comparative causal research. The population in this study were 50 students of the Pariaman City SPNF-SKB Package C Program. The sample in this study amounted to 40 residents studied using cluster random sampling technique. The data collection technique used is documentation. The data analysis technique used is descriptive quantitative. Analysis of the data used quantitatively by using the t-test using SPSS16 software.Based on the results of the research on the learning outcomes of the residents of the Package C Program before the pandemic, the highest was in the very good category, amounting to 29 people with a percentage of 72.5%, of the 40 residents studying the Package C Program before the pandemic and the value of learning outcomes for learning residents during the covid pandemic. the highest is the unfavorable category, totaling 19 learning residents with a percentage of 47.5% of the 40 residents studying the Package C Program during the pandemic. So there are differences in the learning outcomes of learning residents before the Covid pandemic with the learning outcomes of learning residents during the Covid pandemic, meaning that the Ha hypothesis is accepted. It is recommended for the department of education outside the school of Padang State University to use the results of this study as a reference in teaching materials for courses. Keywords: learning outcomes, Pandemic Covid-19